2017
DOI: 10.1126/sciadv.1602899
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus causes testicular atrophy

Abstract: Zika virus replicates in mouse testes and causes testicular atrophy, with implication on sexual transmission and male fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
103
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 46 publications
16
103
1
1
Order By: Relevance
“…To accomplish this, we built a metabolic network containing the biosynthesis pathways of each subclass in our lipidomics dataset (Supplementary Fig. 8a) then surveyed the network for metabolites associated with seven Medical Subject Heading (MeSH) terms selected for their similarity to clinical outcomes of ZIKV infection 6567 . As a consequence of including all compounds and genes from the constituent lipid biosynthesis pathways in our metabolic model (Supplementary Data 5), nearly every node of the resulting disease-metabolite network was a non-lipid compound capable of participating in other aspects of cellular metabolism (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish this, we built a metabolic network containing the biosynthesis pathways of each subclass in our lipidomics dataset (Supplementary Fig. 8a) then surveyed the network for metabolites associated with seven Medical Subject Heading (MeSH) terms selected for their similarity to clinical outcomes of ZIKV infection 6567 . As a consequence of including all compounds and genes from the constituent lipid biosynthesis pathways in our metabolic model (Supplementary Data 5), nearly every node of the resulting disease-metabolite network was a non-lipid compound capable of participating in other aspects of cellular metabolism (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although our studies were focused on protection against trans-placental transmission and fetal infection, the robust responses to the prM-E mRNA and ZIKV-NS1-LAV vaccines indicate they could diminish infection in other target populations and decrease the epidemic force of infection. Immunization of males may be important if the ZIKV-induced damage to the testes reported in mice (Govero et al, 2016; Ma et al, 2016; Uraki et al, 2017) becomes apparent in humans or to prevent sexual transmission. An additional consideration is whether in the context of pregnancy the systemic immunity that is generated by vaccination is sufficient to prevent local vaginal infection and spread via organs of the reproductive tract that occurs during sexual transmission (Khan et al, 2016; Shin and Iwasaki, 2013; Yockey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although these limitations exist, mouse models of ZIKV infection have been instrumental in identifying potential tissue and cellular targets of ZIKV in vivo [44, 59, 60]. However, studies of ZIKV infection in mice have also reported findings such as testicular atrophy, which has not been reported in human clinical cases to date [61]. Both the chick embryo and neonatal pig models may be very useful for testing therapeutics and/or understanding ZIKV infection outcomes in the early neonatal period respectively, and are relatively inexpensive [49, 55].…”
Section: Animal Models Of Zika Virus Infectionmentioning
confidence: 99%